1997
DOI: 10.1007/s001250050679
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetic retinopathy in children and adolescents with IDDM

Abstract: Summary Vision-threatening diabetic retinopathy can be prevented if it is diagnosed before becoming too advanced. Since diabetic retinopathy has been reported to occur only rarely before the end of pubertal development, children and adolescents are seldom included in screening programmes. We invited 780 children and adolescents with insulin-dependent diabetes mellitus diagnosed before the age of 15.0 years (disease duration of < 12 years) and who were older than 9.0 years at the time of examination from eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 19 publications
2
43
1
Order By: Relevance
“…Although not normally present during the first 5 years of Type I diabetes [7], STDR may rarely develop in pre-pubertal patients if they are extremely poorly controlled [8]. PDR is not likely to develop within the first 10 years of diabetes but its incidence reaches about 30 out of 1000 patients per year rapidly afterwards [9,10].…”
Section: Prevalence and Risk Factorsmentioning
confidence: 99%
“…Although not normally present during the first 5 years of Type I diabetes [7], STDR may rarely develop in pre-pubertal patients if they are extremely poorly controlled [8]. PDR is not likely to develop within the first 10 years of diabetes but its incidence reaches about 30 out of 1000 patients per year rapidly afterwards [9,10].…”
Section: Prevalence and Risk Factorsmentioning
confidence: 99%
“…2). Mean age at diagnosis of PDR was 27 years (range: 17-41), and mean diabetes duration was 19 years (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Thirty-two patients (10.9%) had no retinopathy at follow-up.…”
Section: Characteristics Of Study Groupmentioning
confidence: 99%
“…Numerous studies [8,[11][12][13][14][15][16][17][18][19][20] have described the prevalence and incidence of DR in type 1 diabetes and its relationship to various characteristics. However, only a few population-based studies of retinopathy in subjects with childhood-onset type 1 diabetes are available [13,15,19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This age was defined at the start of the programme in 2005 by a report which found that the youngest person to have STDR was 11.9 years old. 9 Previous studies have been carried out to assess DR prevalence in young patients. The majority of these studies showed that a small percentage of patients younger than 12 years developed DR. 7,10,11 The main aim of the audit was to assess whether the current starting age is appropriate in relation to identification of STDR.…”
Section: Introductionmentioning
confidence: 99%